Time-frequency dependency of financial risk and economic risk: Evidence from Greece - Dervis Kirikkaleli (Journal of Economic Structures, 2019)
This study aims to shed some light on the one of the most popular phenomena in the economics and finance literature-nexus between economic growth and financial development-for the case of Greece over 1990Q1 to 2018Q4 within the framework of risk. In other words, this study investigates the causal link between financial risk and economic risk in Greece using wavelet coherence tests while answering the following questions: (i) does financial risk lead to economic risk in Greece and/or does economic risk lead to financial risk in Greece, and (ii) if so, why? The wavelet coherence approach allows the study to capture the long-run and short-run causal linkages among the time series variables since the approach combines time and frequency domain causalities. The findings from wavelet coherence supports the Schumpeter hypothesis since the findings proves that there is unidirectional causality from financial risk to economic risk in Greece (i) between 1995 and 1998; (ii) between 2003 and 2013; (iii) between 2013 and 2017 at different frequency levels. The findings clearly reveal how financial risk is important predictor for economic risk in Greece over the period of 1990-2018.
Keywords: 330; Financial risk; Economic risk; Greece; Wavelet coherence; Causality